Public Perception The Impact Of People Activities in Sand And Stone Mining on Economy and Environment in Nulokla Village Jayapura - Ratang, Sarlota (Advances in Social Sciences Research Journal, 2017)
This research is aimed to determine the public perception towards the impact of people activities in sand and stone mining in Nolokla village, Jayapura, determine the people income levels of sand and stone mining in Nolokla village Jayapura, and the impact which is felt by the miners in terms of the surrounding environment. This research is a survey with descriptive analysis method. The positive impact in term of economics, sand and stone mining in Nolokla is increaing the income of the miners. The gross income of sand miners per day is Rp. 1.037.500, while for stone miners is Rp. 1.365.000. However, the negative impact of the activity is environmental degradation, water flow decrease and critical land.